2022
DOI: 10.1007/s12633-022-02148-x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Upconversion Luminescence Properties of Pr3+-Doped Y2SiO5 Phosphor

Abstract: Ultraviolet-C light has significant application prospects in the fields of disinfection, air purification, etc. Herein, an effective UVC upconversion phosphor Y 2 SiO 5 :Pr 3+ was successfully prepared, as evidenced by the XRD results. The diffuse reflection spectra of Y 2 SiO 5 : Pr 3+ phosphors presented two distinct absorption bands corresponding to the electron transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Y 2 SiO 5 :Pr (I) possesses a band gap of 3.985 eV, and Y 2 SiO 5 :Pr (II) has a band gap of 4.145 eV. These results are slightly smaller than the calculated band gap of pure Y 2 SiO 5 (4.172 eV) but larger than the Yb 3+ -doped Y 2 SiO 5 crystals studied by Zhou et al Therefore, the doping of Pr 3+ induces a reduction in band gaps for the host Y 2 SiO 5 crystal. It is obvious that the energy bands of Y 2 SiO 5 :Pr (I) and Y 2 SiO 5 :Pr (II) are divided into three parts, which contain the conduction bands with energy larger than 6.75 eV, the valence bands with energy smaller than the Fermi level, and the bands at around 4 eV.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…Y 2 SiO 5 :Pr (I) possesses a band gap of 3.985 eV, and Y 2 SiO 5 :Pr (II) has a band gap of 4.145 eV. These results are slightly smaller than the calculated band gap of pure Y 2 SiO 5 (4.172 eV) but larger than the Yb 3+ -doped Y 2 SiO 5 crystals studied by Zhou et al Therefore, the doping of Pr 3+ induces a reduction in band gaps for the host Y 2 SiO 5 crystal. It is obvious that the energy bands of Y 2 SiO 5 :Pr (I) and Y 2 SiO 5 :Pr (II) are divided into three parts, which contain the conduction bands with energy larger than 6.75 eV, the valence bands with energy smaller than the Fermi level, and the bands at around 4 eV.…”
Section: Resultsmentioning
confidence: 53%
“…20 Due to the crystal field interactions of Pr 3+ in the host Y 2 SiO 5 , the 3 H 4 and 1 D 2 states can further split to 9 and 5 Stark levels, respectively. And it could be possible to detect single ions via the 3 nm are due to the transitions of 4f5d → 3 H 4 and 4f5d → 3 H 5 of Pr 3+ ions. 3 For the detailed transition spectrum, Cheng-Lin et al reported the optical properties of the Y 2 SiO 5 :Pr crystal, including absorption spectrum, excitation spectrum, and fluorescence attenuation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pr 3+ -doped Y 2 SiO 5 and Li 2 SrSiO 4 show efficient UVC upconversion between 250 and 340 nm when excited by a 450 or 460 nm laser. 10,11 Moreover, Li 2 SrSiO 4 :Pr 3+ can effectively inactivate bacteria within 10 min, 11 which proves that silicate phosphors are promising matrices for UVC-based antibacterial applications.…”
Section: ■ Introductionmentioning
confidence: 92%